Konsep Pendidikan Holistik Dalam Peningkatan Kemampuan Literasi dan Numerasi Siswa Sekolah dasar - AMALIYAH, RIZKI (Journal of Contemporary Issue in Elementary Education, 2025)
A compressive technique to reconstruct education in all its facets is known as holistic education. A qualitative descriptive research technique combined with a literature study approach was the research methodology employed in this study. This approach entails gathering, examining, documenting, and evaluating information from a variety of reference sources that are pertinent to the study's goals. This approach is employed in this study to better comprehend the idea of holistic education in enhancing elementary school students' reading and numeracy skills. According to the study's findings, elementary school students' literacy and numeracy can be improved through the use of holistic education. However, many educational institutions have not fully adopted this approach, and other studies have noted a number of implementation challenges, such as a lack of dedication to collaboration among related sectors.